PENERAPAN METODE PEMBELAJARAN INDEX CARD MATCH UNTUK MENINGKATKAN HASIL BELAJAR PENJASKES SISWA KELAS V SD NEGERI 002 BATU BERSURAT - Asnimar Asnimar (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2017)
This research is motivated by the result of observation of the researcher on the students of class V SD Negeri002 Batu Bersurat on the learning process of Penjaskes in class. From the observation it is known that there arestill many students pay less attention to the explanation of the teacher when delivering the material in the class,the students are only silent although the teacher asked for lesson material dimenegrti by students. studentlearning outcomes are low that is 62.5% complete from 24 students with minimal mastery criteria (KKM) is 70.Students classical thoroughness din seniatakan not complete. This study aims to find out that the application ofindex card match method can improve the learning outcomes of Penjaskes in grade V SD Negeri 002 BatuBersurat students. This research was conducted in class V SD Negeri 002 Batu Bersurat. This research wasconducted from September 2016 until October 2016. The subjects of this study are the students of class V withthe number of students 24 students consisting of 11 female students and 13 male students. This form of researchis a classroom action research (PTK). The results obtained that the application of index card match learningmethod can improve learning outcomes Penjaskes in grade V SD Negeri 002 Batu Bersurat 2016/2017 academicyear. Learning outcomes before the PTK is 66.7 with the category of less and classical completeness of 62.5%premises unfinished category. The result of learning cycle I meeting 1 is 75.8 with sufficient category andclassical completeness of 87.5% with complete category. The results of learning cycle I meeting 2 is 79.2 withsufficient category and classical completeness of 91.7% with the category of due diligence. The result oflearning cycle II meeting 3 is 82.1 with good category and classical completeness equal to 95.8% with completecategory. The result of learning cycle II meeting 4 is 87.9 with good category and classical completeness equalto 100% with complete category.